Targetable micelleplex hydrogel for long-term, effective, and systemic siRNA delivery - Kim, Young-Min; Song, Soo-Chang (ELSEVIER SCI LTD, 2014)
We developed a targetable micelleplex hydrogel as a new efficient systemic siRNA delivery material that functions as a targetable gene carrier, and a hydrogel capable of controlled release to overcome drawbacks of multiple administrations of systemic siRNA carriers due to decreased fluctuation of them in the serum. The micelleplexes, complexes between polymeric micelles and siRNAs could turn into gel after subcutaneous injection and be slowly released from the gel. The released micelleplexes selectively accumulated in the tumor and showed anti-tumor effect due to gene silencing for an extended period of time with only one injection in anywhere in vivo model. Moreover, the duration of therapy can be controlled by adjusting the amount and properties of the hydrogel. Therefore, this micelleplex hydrogel is expected to be a new effective siRNA delivery material for systemic long-term gene silencing. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: SUSTAINED-RELEASE